Conservation management of small populations of elephants (Loxodonta africana, Blumenbach 1797) in South Africa using genetics and population modelling - marina.alais@up.ac.za (University of Pretoria, 2013)
Dissertation (MSc (Genetics))--University of Pretoria, 2010.